Potential Review Assessment with 9 Grid Talent Management Boxes there are PT X Employees - Ayuningtyas, Shenna Mentari; Adiati, Rosatyani Puspita (Universitas Pamulang, 2025)
Potential review is a component of talent management that aims to identify the extent to which an individual can be projected into a higher position within an organization. This study aims to understand the implementation of potential review assessment at PT X using the 9 Box Grid talent mapping method. The subject of this study is an employee of PT X who is being considered for promotion to the position of Senior Officer of HR and Organizational Planning, Data collection was conducted using a combination of work test, interview, and psychological tests. Data analysis was carried out using a descriptive qualitative approach. The results indicate that the subject was categorized into the